Pengaruh demografi terhadap kesediaan penduduk bagi pelaksanaan projek "unity alarm" di kawasan perumahan jajahan Kota Bharu Kelantan - Mohammad Zubir, Abu Bakar (2020)
The speed of urbanization in the country has indirectly contributed towards the increasing number of crime rates. Due to this, there are issues raised by the residents about the level of readiness for installing new equipment or innovations, namely the unity alarm; preventing crime in their homes. In this study, the question of the level of preparedness among the residents is measured through three constructs namely knowledge, feelings and actions of residents to determine their level of preparedness in the use of unity alarms to prevent criminal behavior. This study was conducted in the district of Kota Bahru, Kelantan with the selection of three types of housing locations namely the luxury, the medium cost and the low cost housing. This study applied the quantitative method by distributing simple random questionnaires to 384 households (respondents) with a distribution of 128 respondents for each household Descriptive and one-way ANOVA analyses were carried out on the collected data to answer the three research objectives. The overall study found that residents of the three types of housing namely luxury, medium cost and low cost were less satisfied with the existing crime prevention methods, while the level of preparedness using residential alarms showed that residents of luxury and medium cost housing were more likely to use unity alarm than residents in the low cost housing areas. The results of the study on the level of readiness based on the knowledge, feelings and actions of the use of unity alarm found that the mean value was 2.76 for the three types of housing (luxury, medium cost and low cost housing). Furthermore, the results identified population demographic differences in the level of readiness through the construction of age, race, household income and the number of households showed there was zero difference in population readiness to use unity alarms in their homes. However, there were two demographic constructs that showed differences in the categories of residential areas (luxury, medium and low cost housing) and respondents educational level that determined differences in residents’ readiness to use unity alarms in their homes. Therefore, it is hoped that this study will help residents better prepare for the implementation of the unity alarm project for crime prevention efforts and realize the goals of the National Unity Policy run by the Department of National Unity and National Integration (JPNIN).